EFEK PERUBAHAN LABA AKUNTANSI DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM - Riza Praditha; Indah Pusvita Sari; Diah Ayu Gustiningsih; Jamaluddin Majid (Jurnal Riset Akuntansi, 2023)
This study aims to analyze the effect of accounting earnings and operating cash flow on stock returns. The population in this study are companies listed on the Indonesia Stock Exchange. The sample used the purposive sampling method with the observation year 2017-2020. The results showed that accounting profit proved to have a positive and significant effect on stock returns. This means that the greater the accounting profit earned by the company, the greater the stock return generated. Different results are shown in the results of the operating cash flow test where the results show a positive but not significant effect on stock returns. These results have implications for the accounting profit presentation policy, in which the company is expected to be able to maximize the acquisition of accounting profit in order to increase the acquisition of stock returns.